Grant family reunion slated (Raton, NM Raton Range, 1980)
This article is about plans for a Grant family reunion to be held in August and about Victor Grant and Geno Pacheco attending a two-day Conference of the New Mexico Museum Association in Taos.
Newspaper article
Mater List Item # 43
File location is in the New Mexico File Cabinets
Keywords: Grant, Victor; Grant, George; Pacheco, Geno; Fellowship Hall; Methodist Church; Family Reunions; Family Visitors; Museums; Exhibits; Cimarron, New Mexico